1995
DOI: 10.1159/000292409
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Ultrasonographic Morphology in Polycystic Ovarian Syndrome

Abstract: To assess the morphological findings based on transvaginal ultrasound, the ovarian volume and the number and size of small follicles were studied in 47 patients with polycystic ovarian syndrome (PCOS) diagnosed clinically. Thirty normal volunteers served as controls. The mean ovarian volume (10.3 ml) and number of follicles (10.6) in patietns with PCOS were significantly higher than those of controls. An ovarian volume > 6.2 ml and follicles > 10 with a diameter of 2–8 mm were the most prominent features in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Although, some investigators like Dunaif et al resulted that for the diagnosis of the syndrome, polycystic morphology is not initially essential ( Dunaif, 1997 ). But Adams et al (1985) described that the most sensitive diagnostic marker for PCOS seen by vaginal ultrasound, even, Giuseppe Loverro claimed that ultrasound measurement of ovarian stroma may predict hyperandrogenism degree; prothrombotic factors and cardiovascular risk in patients with PCOS ( Loverro et al, 2010 ) and Takahashi et al (1995) reported that transvaginal ultrasound criteria of PCOS observed in 94% of PCOS women.…”
Section: Discussionmentioning
confidence: 99%
“…Although, some investigators like Dunaif et al resulted that for the diagnosis of the syndrome, polycystic morphology is not initially essential ( Dunaif, 1997 ). But Adams et al (1985) described that the most sensitive diagnostic marker for PCOS seen by vaginal ultrasound, even, Giuseppe Loverro claimed that ultrasound measurement of ovarian stroma may predict hyperandrogenism degree; prothrombotic factors and cardiovascular risk in patients with PCOS ( Loverro et al, 2010 ) and Takahashi et al (1995) reported that transvaginal ultrasound criteria of PCOS observed in 94% of PCOS women.…”
Section: Discussionmentioning
confidence: 99%
“…an ovarian area >5.5 cm 2 unilaterally or bilaterally) as a morphological indicator of PCOS, since it can be more easily quanti®ed and correlates closely with the stromal hypertrophy (Dewailly et al, 1994). Others came to the same conclusions by using ovarian volume (Pache et al, 1992;Takahashi et al, 1995;VanSantbrink et al, 1997). There is more controversy about the increased number of follicles as a morphological predictor of PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…24 It is more than eight discrete of < 10 mm diameter in one plain of the ovary, usually arrayed around, but sometimes scattered throughout, an enlarged, hyperechogenic, central stroma, by transabdominal ultrasonography, 25 The number of small cysts in one ovary is 10.6 ± 2.1 in PCOS patients, it is significantly higher compared with 3.5 ± 2.1 in normal control. 26 They also demonstrated that an increase of the number of small cysts is related to the frequency of menstrual disturbances. 27 There are two types of PCO as reflecting histopathological differences.…”
Section: Polycystic Ovary Syndromementioning
confidence: 97%